Identification and Adoption of Themes in The Big Bang Theory Sitcom to Foster Academic Cultural Competencies of Doctoral Students in English for Academic Conversation Classroom - Lasekan, Olusiji (Frontiers in Psychology, 2021)
The primary purpose of this study is to identify academic cultural themes in the popular television sitcom The Big Bang Theory in order to enhance doctoral students’ awareness and acquisition of Ph.D. competencies through formalized and explicit instruction. The secondary aim is to assess the impact of the selected academic themes on doctoral students’ acquisition of Ph.D. competencies in an English for Academic Conversation (EAC) classroom. Drawing upon the concept of thematic learning instruction, a qualitative research method involving six clusters of Ph.D. competency reference framework developed by Durette and others was adopted to identify the academic cultural themes depicted by the sitcom’s main characters. This is followed by evaluating the effectiveness of an EAC course in fostering learners’ Ph.D. competencies using selected identified academic cultural themes. The result showed that the sitcom’s main characters demonstrate the personal and professional skills commonly possessed by a competent academic as an individual or group. This is evidenced as all the thirty-four identified skills traverse the six clusters of Ph.D. competencies devised by Durette and colleagues in 2016. Also, the impact assessment results revealed that the course fostered learners’ Ph.D. competencies as they shared knowledge, past experience, and action plans of every selected academic theme. This work contributes to existing knowledge of doctoral competencies vital to promoting competency-based Ph.D. programs in higher education.